2012
DOI: 10.12799/jkachn.2012.23.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychospiritual Care Need by End-of-life Stages among Non-cancer Patient at Home: Based on the Importance and Difficulty of Care Need

Abstract: Purpose: This study was conducted to assess needs at each end-of-life care stage and to analyze importance and difficulty of care needs for home care nursing among non-cancer patients. Methods: We used a retrospective design. Total eligible patients were 117 at the ages of 40 and over, who continuously received home care nursing throughout beginning, stable, and near death stages, and finally died at home from January 1, 2006 to December 31, 2006. Descriptive statistics, Cochran's Q test, Friedman's test were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…These problems could be, however, due to the severity of patient conditions rather than the simple difference between cancer and noncancer patients. This was supported by Lee and Kim (2012), who reported that the basic needs related to "assistance for daily life activities" are high for noncancer patients who are at the beginning of the end-of-life stage, and that the need for nursing due to "deterioration of physical symptoms" increases as the patient approaches death. In this study, however, "supporting fundamental needs" was found to be high for patients as their severity increased.…”
Section: Discussionmentioning
confidence: 89%
“…These problems could be, however, due to the severity of patient conditions rather than the simple difference between cancer and noncancer patients. This was supported by Lee and Kim (2012), who reported that the basic needs related to "assistance for daily life activities" are high for noncancer patients who are at the beginning of the end-of-life stage, and that the need for nursing due to "deterioration of physical symptoms" increases as the patient approaches death. In this study, however, "supporting fundamental needs" was found to be high for patients as their severity increased.…”
Section: Discussionmentioning
confidence: 89%